Pathological Investigation of Lumpy Skin Disease in Cattle from Sleman, Indonesia - Kristianingrum, Yuli Purwandari; Winarsih, Sugi; Sutrisno, Bambang; Widyarini, Sitarina; Sugiyono, Sugiyono; Untari, Tri (Universitas Airlangga, 2025)
In early 2023, there was an outbreak of lumpy skin disease (LSD) in cattle in Indonesia, with particularly high prevalence in Sleman, Special Region of Yogyakarta, Indonesia. Since then, cases of this disease have been increasing, causing significant economic losses to cattle and buffalo farmers. This study aimed to investigate the pathological changes caused by LSD virus infection in various organs of Sleman cattle. We investigated 15 animals from 10 farms. Skin samples were taken by biopsy. ELISA testing was performed on serum samples. We also performed necropsies on two LSD infected cow carcasses to observe the macroscopic and microscopic effects of the virus. During the necropsies, samples were obtained from skin nodules, skeletal muscle, and internal organs (lung, liver, kidney, lymphatic nodes, spleen, and digestive organs). These were subjected to histopathological examination using hematoxylin and eosin staining. Among the live animals, fever, lethargy, hypersalivation, and lacrimation were the most common clinical signs. Our qualitative descriptive analysis of the pathological changes, clinical signs, and ELISA results showed that LSD infection in cattle causes mild to severe damage to various organs. Our macroscopic examinations found that affected animals had skin nodules of varying sizes over the entire body. We observed mild to severe inflammation and hemorrhage in the internal organs, including the skeletal muscles, spleen, liver, heart, rumen, reticulum, abomasum, and small intestine. Based on this investigation, we conclude that, in addition to its effects on the skin, LSD causes pathological changes in various internal organs.